Reverberant 3D optical coherence elastography maps the elasticity of individual corneal layers - Fernando Zvietcovich (Nature Portfolio, 2019)
Elastic mapping of individual layers of the cornea with elastography uses Lamb waves, which are dependent on the thickness of each layer and the direction of propagation. Here the authors present Reverberant 3D Optical Coherence Elastography to measure elasticity of single layers using waves propagating in all directions.